Clinical practice guidelines for management of dual antiplatelet therapy in patients with noncardiac surgery: A critical appraisal using the AGREE II instrument. (23rd December 2021) - Wang, Xin; Tang, Borui; Liu, Ying; Wang, Xinrui; Wang, Shihui; An, Zhuoling; Wang, Huaguang
Abstract: What is known and objective: Despite the availability of clinical practice guidelines (CPGs), there are considerable differences in their recommendations in the perioperative management of stented patients who need elective noncardiac surgery. Our aim was to systematically review the quality of CPGs for perioperative management of dual antiplatelet therapy (DAPT) and summarize the recommendations. Methods: A systematic search for perioperative DAPT guidelines was conducted on PubMed, Embase and websites of guideline organizations and professional societies until 4 February 2021. Independently, two assessors appraised the quality of CPGs using the Appraisal of Guidelines for Research & Evaluation II (AGREE II) instrument and extracted the data. Recommendations were summarized, and a comparative study was conducted to analyse the consistency among guidelines. Results and discussion: A total of 10 guidelines fulfilled our inclusion criteria. The domain of scope and purpose and clarity of presentation obtained the highest median scores, while the domain of stakeholder involvement and rigour of development obtained the lowest median scores. Three guidelines (ACCP, ESC/ESA and ACC/AHA) with a score of at least 60% in most AGREE II domains were recommended. Recommendations across perioperative management of DAPT guidelines were inconsistent. What is new and conclusion: The ACCP, ESC/ESA and ACC/AHA CPGs were recommended. There is a need for high‐quality prospective studies assessing different management strategies on this issue. Given the lack of consensus, the results of this study will help to guide perioperative dual antiplatelet management strategies for patients with coronary stents who are undergoing noncardiac surgery. Abstract : The ACCP, ESC/ESA and ACC/AHA CPGs were recommended. There is a need for high‐quality prospective studies assessing different management strategies on this issue. Given the lack of consensus, the results of this study will help to guide perioperative dual antiplatelet management strategies for patients with coronary stents who are undergoing noncardiac surgery.